Temperature and fire controls on vegetation dynamics in Northern Ural (Russia) boreal forests during the Holocene based on brGDGT and pollen data. (1st April 2023) - Barhoumi, Chéïma; Ménot, Guillemette; Joannin, Sébastien; Ali, Adam A.; Ansanay-Alex, Salomé; Golubeva, Yulia; Subetto, Dmitry; Kryshen, Alexander; Drobyshev, Igor; Peyron, Odile
Abstract: Boreal vegetation is influenced by multiple factors such as climate and fire, but interactions between long- and short-term effects of climate upon fire activity are complex and remain poorly studied, especially in Eurasia. To understand the relationships between climate, fire and vegetation in Eurasia, we reconstruct the climate changes during the Holocene for the western section of the Northern Urals region, in the southern part of the Republic of Komi. We relate these temperature reconstructions to pollen and charcoal records from the same region (Yaksha site, Republic of Komi, Russia). We use here a combined approach based on pollen and molecular biomarkers (branched Glycerol Dialkyl Glycerol Tetraethers or brGDGTs) to provide independent estimates of past temperatures. Our objectives were: (1) to understand the relationships between climate, fire, vegetation and human activity during the Holocene at the local scale of Yaksha and (2) to provide a robust regional-scale climatic reconstruction of the southern part of the Republic of Komi. Our study shows that climate had a major influence on the regional vegetation between 10, 000 and 4000 cal Yr BP. Subsequently, fire activity had a joint and growing impact on vegetation dynamics between 4000 and 600 cal Yr BP. Finally, from 600 until the present (2016 CE), human presence and activities had a greater impact on the fire regime and vegetation than earlier in time, and combined with climate to influence the dynamics of the boreal forest. At the regional scale of the Republic of Komi and the local scale of Yaksha, the Holocene Thermal Maximum was detected between 6800 and 4000 cal Yr BP, using pollen-based temperature estimates but at 4000 cal Yr BP using brGDGT calibrations applied from the literature. These results are consistent with evidence from neighboring regions in the Eurasian boreal biome which were studied for different proxies (pollen, chironomids), and also with reference to climate models (General Circulation Models). Highlights: Holocene climate reconstruction inferred from pollen and brGDGTs for the Republic of Komi (Russia). Major influence of climate on regional vegetation between 10, 000 and 4000 cal. yr BP. Growing impact of fire activity between 4000 and 600 cal.yr BP. From 600 until present, human activities had greater impact on fire regime and vegetation. Holocene Thermal Maximum between 6800 and 4000 cal. yr BP according pollen but at 4000 cal. yr BP according brGDGT.